2015
DOI: 10.1515/pomr-2015-0069
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Thermal Energy Storage According to the Convention of Bond Graphs (Bg) and State Equations (Se)

Abstract: The main advantage of the use of the Bond Graphs method and State Equations for modeling energy systems with a complex structure (marine power plants, hybrid vehicles, etc.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Doubts arise when creating BG models of thermal processes, especially regarding the new elements introduced into these models as a dual battery [1,27] (2-port) or the modeling of thermal processes using so-called "pseudo Bond Graphs" [1,3,8,10,26,27]. In [2,3] a new method of modeling thermal processes has been presented using only elements introduced in the basic BG theory form modeling of mechanical, hydraulic and electrical processes. In these works the analysis of causality was deliberately not used since according to the theory proposed in separate models of thermal processes, there was no possibility of a conflict of causality [3].…”
Section: Fig 1 Diagram and Designation Of Bg Model Energy System To mentioning
confidence: 99%
See 4 more Smart Citations
“…Doubts arise when creating BG models of thermal processes, especially regarding the new elements introduced into these models as a dual battery [1,27] (2-port) or the modeling of thermal processes using so-called "pseudo Bond Graphs" [1,3,8,10,26,27]. In [2,3] a new method of modeling thermal processes has been presented using only elements introduced in the basic BG theory form modeling of mechanical, hydraulic and electrical processes. In these works the analysis of causality was deliberately not used since according to the theory proposed in separate models of thermal processes, there was no possibility of a conflict of causality [3].…”
Section: Fig 1 Diagram and Designation Of Bg Model Energy System To mentioning
confidence: 99%
“…In [2] it was found that the Energy storing models of thermal processes, as in the basic theory, should be in the form of a graph (bond) with a single node (1-port). The concept of an energy transducer has been introduced [2,3] (fig.…”
Section: Fig 1 Diagram and Designation Of Bg Model Energy System To mentioning
confidence: 99%
See 3 more Smart Citations